2002
DOI: 10.1096/fj.01-0552com
|View full text |Cite
|
Sign up to set email alerts
|

The pro‐ or antiangiogenic effect of plasminogen activator inhibitor 1 is dose dependent

Abstract: Plasminogen activator inhibitor 1 (PAI-1) is believed to control proteolytic activity and cell migration during angiogenesis. We previously demonstrated in vivo that this inhibitor is necessary for optimal tumor invasion and vascularization. We also showed that PAI-1 angiogenic activity is associated with its control of plasminogen activation but not with the regulation of cell-matrix interaction. To dissect the role of the various components of the plasminogen activation system during angiogenesis, we have ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
222
3
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(239 citation statements)
references
References 32 publications
11
222
3
3
Order By: Relevance
“…Furthermore, these in vivo observations are amply supported by results obtained in vitro in the mouse aortic ring model [96]. The essential role of PAI-1 in angiogenesis may be explained by the multifunctional nature of PAI-1 (see above).…”
Section: Unexpected Role Of Pai-1 In Tumor Angiogenesismentioning
confidence: 60%
See 2 more Smart Citations
“…Furthermore, these in vivo observations are amply supported by results obtained in vitro in the mouse aortic ring model [96]. The essential role of PAI-1 in angiogenesis may be explained by the multifunctional nature of PAI-1 (see above).…”
Section: Unexpected Role Of Pai-1 In Tumor Angiogenesismentioning
confidence: 60%
“…In the aortic ring assay, no vessels form from PAI-1-deficient animals. Addition of exogenous recombinant PAI-1 at a physiological concentration restores microvessel sprouting, while at 'therapeutical' concentrations, angiogenesis is inhibited [96]. Similarly, PAI-1 inhibits bFGF-induced angiogenesis when added at high concentrations [98].…”
Section: Unexpected Role Of Pai-1 In Tumor Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it has been reported that tumour angiogenesis is drastically impaired in mice with targeted disruption of the PAI-1 gene (Bajou et al, 1998. A few other model system studies have also suggested a proangiogenic role of PAI-1 (Lambert et al, 2001;McMahon et al, 2001;Devy et al, 2002). In particular, the possible role of uPA and PAI-1 in angiogenesis was of interest in the preparation of the present study.…”
Section: Discussionmentioning
confidence: 78%
“…In several cell culture and animal model systems, PAI-1 has been found to have a proangiogenic effect (Bajou et al, 1998Lambert et al, 2001;McMahon et al, 2001;Devy et al, 2002). However, the clinical significance of the biological interaction of angiogenesis and the plasminogen activator system is unknown.…”
mentioning
confidence: 99%